(905) Allocation of Resources with Unlimited Supplies of Labour. '' An Application in the Case of Egypt'' تخصيص الموارد مع إمدادات غير محدودة من العمالة ”تطبق في حالة مصر“ - Amr Mohie Eldin. (INP, 2024)
This paper attempts to critically examine development theories based on unlimited supplies of labor, such as those proposed by A. Lewis, R. Nurkse, and Ranis & Fei. These growth models can be analyzed on two levels: theoretical and practical. The aim is not to assess the logical consistency of these models, as they are consistent at an abstract level, but rather to evaluate their practical applicability, particularly in the context of the Egyptian economy.